Remediasi Pembelajaran Biologi bagi Peserta Didik Kelas X IPS dan XI MIPA : Praktik Pengabdian Berbasis Pendidikan - Susilawati, Puspita Ratna; Pasassung, Irenne Odly Kathleen; Saputro, Hardian Nico Thomas; Sulistyani, Niluh; Krisnamurti, Cyrenia Novella (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service aims to help Santa Maria Yogyakarta Dormitory students overcome learning difficulties through a biology learning remediation program. The method of implementing this community service used tutoring. The service participants consisted of students from class X IPS and XI MIPA who lived at the Santa Maria Dormitory in Yogyakarta. The evaluation instrument for this activity uses closed and open questionnaires, which are analyzed descriptively. The service results showed that students' problems are difficulty understanding the material, feeling lazy, and bored with studying biology. This problem could be overcome by applying fun learning methods and media. Student responsed to the biology learning remediation program were classified as very high, and the impact felt by students is relatively high.